Measurement of Blood Pressure in Children : A Systematic Approach - Das, Jagadish C (Journal of Chittagong Medical College Teachers’ Association, 2012)
Measurement of blood pressure properly is important. Prevalence of hypertension in children is not less. Morbidity and mortality of hypertension cannot be ignored. Blood pressure (BP) should be measured systematically among children over 3 years old who are seen in a medical setting. Among <3 years children, blood pressure should be measured in special circumstances. Various methods of blood pressure measurement are existent. Though ambulatory blood pressure monitoring (ABPM) has some advantages, over all sphygmomanometry is the preferred method. Conventional cuff measurement and ABPM cannot be used interchangeably. For correct recording of BP a cuff that is appropriate to the size of the child’s supper arm is needed. Elevated BP must be confirmed on repeated visits before declaring a child as hypertensive. Measures obtained by oscillometic device that exceed the 90th percentile should be repeated by auscultation. JCMCTA 2011; 22(2): 57-59